The Frequency of Exposing To Violence And Its Effects on State and Trait Anxiety Levels Among The Doctors and Nurses Working In Samsun Psychiatry Hospital - Gokce, Tugrul; Dundar, Cihad (Annals of Medical Research, 2021)
None